Changing preservice science teachers' beliefs through constructivist technology-aided learning - Navaja, Lorna Milly Avila (Animo Repository, 2005)
The study aimed to examine how the introduction of a constructivist technology aided instructional unit influenced preservice teachers beliefs to adopt constructivist teaching practices and utilize technology for science teaching. The class was taught using a tutorial from the internet, a computer simulation and some movie clips in a constructivist manner. The respondents were forty-four, 3rd year education students in an intact class. Six of them were chosen for the qualitative portion of the study. The study categorized preservice teachers beliefs into pedagogical beliefs, capability beliefs and context beliefs. The data were gathered through questionnaires, journals and interviews. Prior to instruction, the questionnaires were administered to determine their prior beliefs and preconceptions on teaching, learning and computer use in the classroom and their understanding of basic science concepts. After their participation in the instructional unit, changes in their beliefs and preconceptions were determined through the posttest. Semi structured interviews and journal writing were done to further examine the students answers to the questionnaires. Changes in their pedagogical beliefs and context beliefs using the paired t-test were not significant. Their capability beliefs showed significance in one instrument. Data derived from the General Science Questionnaire, however, showed that the respondents participation in the instructional unit has resulted in a significant increase in their understanding of basic science concepts . The Pearson Product Correlation, used to determine the association between the respondents pedagogical beliefs and their use of computers for instruction were not consistent. The qualitative results from their journals and interviews, however, indicated that the participants underwent conceptual change at varying levels as a result of their participation of the technology-aided instructional unit. Their dissatisfaction with their existing conception, understanding of the constructivist concepts and acknowledged the viability of the constructivist technology-assisted instructional unit, were evident in their writings and interviews. These results showed that the subtle changes of beliefs and conceptions of the participants, which were not seen using quantitative methods, were shown in the qualitative results.